Pengaruh Penggunaan Digital Marketing pada Penjualan Produk UMKM Menggunakan Model UTAUT (Unified Theory of Acceptance and Use of Technology) - Leily Nur Indah Fitriana; Nur Syakherul Habibi; Moh. Aminollah Hamzah (ProBank, 2025)
The MSME sector plays a crucial role in Indonesia's economic growth. MSMEs contribute significantly to job creation, income generation, and economic growth. This research, conducted in Pamekasan Regency, will provide valuable insights for the government and other stakeholders in designing appropriate policies and programs to support MSMEs in effectively adopting digital technology. To identify factors influencing the acceptance and use of digital marketing among Micro, Small, and Medium Enterprises (MSMEs) in Pamekasan Regency, the Unified Theory of Acceptance and Use of Technology (UTAUT) model can be used as a conceptual framework. Based on the UTAUT model, technology acceptance and use are influenced by four main factors: performance expectations, business expectations, social influence, and supporting conditions. This research will analyze the influence of these four factors on the acceptance and use of digital marketing among MSMEs in Pamekasan Regency, as well as their impact on product sales.